2003
DOI: 10.1021/jf020604h
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-Converting Enzyme Inhibitory Peptides in a Hydrolyzed Chicken Breast Muscle Extract

Abstract: The blood pressure of spontaneously hypertensive rats (SHRs) decreased after oral administration of an extract prepared from chicken breast muscle, falling maximally to 50 mmHg lower than before. This effect continued for at least 4 h after administration. The peptides possessing hypotensive activity in the chicken extract were examined by measuring the inhibitory activity (IC(50)) against angiotensin I-converting enzyme (ACE). The inhibitory activity of the chicken extract was 1060 mg%, whereas the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 25 publications
2
74
0
2
Order By: Relevance
“…Multifunctional bioactivities of chicken essence have recently been reviewed (38). Carnosine, anserine and taurine, which are abundantly included in chicken, have been reported to be involved in blood flow and blood pressure changes (39)(40)(41)(42). Our findings suggest that defatted chicken facilitates both thyroid hormone signaling and energy metabolism except for lipid metabolism.…”
Section: Discussionmentioning
confidence: 59%
“…Multifunctional bioactivities of chicken essence have recently been reviewed (38). Carnosine, anserine and taurine, which are abundantly included in chicken, have been reported to be involved in blood flow and blood pressure changes (39)(40)(41)(42). Our findings suggest that defatted chicken facilitates both thyroid hormone signaling and energy metabolism except for lipid metabolism.…”
Section: Discussionmentioning
confidence: 59%
“…We found that a peptide (Gly-Phe-Hyp-Gly-Thr-Hyp-Gly-LeuHyp-Gly-Phe) derived from type I collagen obtained from a hydrolyzed chicken breast muscle extract inhibited angiotensin-I converting enzyme (ACE) and lowered blood pressure in spontaneously hypertensive rats (SHRs). 4,5) We have also reported that chicken collagen hydrolysate obtained from type I collagen in chicken legs had the same effects, due to an ACEinhibitory peptide (Gly-Ala-Hyp-Gly-Leu-Hyp-GlyPro). 6) There is no evidence of these effects of chicken collagen hydrolysate in humans.…”
mentioning
confidence: 78%
“…Oxidation by free radicals is also one of the primary mechanisms of quality deterioration in foods and especially in meat products, which also limits shelf-life and makes meat potentially dangerous for consument's health (Simitzis et al, 2009;Bošković et al, 2013;Udenigwe and Ashton, 2013). In order to prevent or to retard lipid oxidation, a number of synthetic antioxidants, such as butylated hydroxyanisole (BHA), butylated hydroxutoluene (BHT), tert-butyl hydroquinone (TBHQ) and propyl gallate (PG) are added to food (Saiga et al, 2003a;Di Bernardini et al, 2011;Ngo et al, 2012). Their use may have negative infl uence on human health which is why food industry tends to fi nd natural alternatives to synthetic antioxidants.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Their use may have negative infl uence on human health which is why food industry tends to fi nd natural alternatives to synthetic antioxidants. (Saiga et al, 2003a;Sakanaka and Tachibana, 2006;Kim et al, 2001;Di Bernardini et al, 2011). One of such possibilities is use of peptides from food sources, which have some advantages, compared to synthetic antioxidants.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%